Genetic variability of three cassava traits across three locations in Ghana - Boakye-Peprah, B.; Ofori , K.; Asante, I.; Parkes, Elizabeth Y. (Academic Journals, 2013)
A study was conducted to assess the extent of genetic variability, broad-sense heritability and correlations for fresh root weight, root number and top weight of five cassava genotypes across three locations in 2 years. Combined analysis of variance revealed highly significant genotypic effect for all the traits. Genotype x environment interaction was also significant for all the traits studied indicating considerable but, varying response of the genotypes to the environments. High broad-sense heritability and genetic advance as percent of the mean were observed for fresh root weight, suggesting that the trait is primarily under genetic control and that a simple recurrent phenotypic selection scheme would be rewarding. Phenotypic coefficients of variation values were larger than their corresponding genotypic coefficient of variation values for all traits. Correlations between the three traits were highly significant and positive indicating that simultaneous progress for the three traits is feasible.